Environmental education - De, Anil K. (Anil Kumar), 1927- (New Age International (P) Ltd., 2004)
About the Book: Designed in terms of the Polytechnic syllabus for students of the N.E. region and also NEHU syllabus on Environment, this book is addressed to all Polytechnic students for Environmental education and culture. In simple and lucid style, the book introduces the basic concepts of environment, physical and human and explains its various dimensions-ecology, pollution, public health, resource conservation and management, etc. Highlights of the book: Exposure to basic concepts of environment in its multidimensional aspects. Simple, lucid treatment of the core areas keeping sc.